Defining and protecting meta privacy: A new conceptual framework within information privacy - Skinner, Geoffrey; Han, Song; Chang, Elizabeth (IEEE Computer Society Press, 2006)
When considering information security and privacy issues most of the attention has previously focused on data protection and the privacy of personally identifiable information (PII). What is often overlooked is consideration for the operational and transactional data. Specifically, the security and privacy protection of metadata and metastructure information of computing environments has not been factored in to most methods. Metadata, or data about data, can contain many personal details about an entity. It is subject to the same risks and malicious actions personal data is exposed to. This paper presents a new perspective for information security and privacy. It is termed Meta Privacy and is concerned with the protection and privacy of information system metadata and metastructure details. We first present a formal definition for Meta Privacy, and then analyze the factors that encompass and influence Meta Privacy. In addition, we recommend some techniques for the protection of Meta Privacy within the information systems. Further, the paper highlights the importance of ensuring all informational elements of information systems are adequately protected from a privacy perspective.